Implicit analysis of the transient water flow with dissolved air - J. Twyman (Ingeniería del Agua)
The implicit finite-difference method (IFDM) for solving a system that transports water with dissolved air using a fixed (or variable) rectangular space-time mesh defined by the specified time step method is applied. The air content in the fluid modifies both the wave speed and the Courant number, which makes it inconvenient to apply the traditional Method of Characteristics (MOC) and other explicit schemes due to their impossibility to simulate the changes in magnitude, shape and frequency of the pressures train. The conclusion is that the IFDM delivers an accurate and stable solution, with a good adjustment level with respect to a classical case reported in the literature, being a valid alternative for the transient solution in systems that transport water with dissolved air.